Observatório de política exterior (OPEx) - Ferreira, Amanda [UNESP]; Almeida, Adriane Gomes Fernandes de [UNESP]; Mei, Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Observatory of Foreign Policy (OPEx) is an extension project coordinated by Compared Study Group on Foreign and Defense (COPEDE / GEDES-SE), Faculty of Humanities and Social UNESP- Franca, in partnership with with the Federal University Sergipe, with the National University of Rosario (Argentina) and the International Relations Program at the Universidad de la Republica (Uruguay). Its goal is to disseminate information on foreign policy seeking to provide data to input decisions in public policy, research and academic education. The team UNESP- Franca prepares weekly reports on the foreign policy of Brazil and Venezuela, through the read-back of news about the theme conveyed in daily newspapers in both countries. Besides the production of reports, the team is responsible for organizing the following monthly events: reading meetings where is discussed and analyzed texts about foreign policy and related issues; and CineGEDES, together with the Centre for Defence and Armed Forces and the Scenario Development Group Prospective (both also linked to GEDES), an event whose purpose is to promote discussion on foreign policy, defense and international security among group members from a film or documentary. . OPEx is distributed electronically and your current list of subscribers includes more than 1,800 addresses, both personal and institutional, can the content of the reports also be accessed through the group of pages in social networks Facebook (/observatoriodepoliticaexterior) and Twitter (@opex_unesp). In 2009, the OPEB won an award for best extension project in the Humanities at the V Congress of the UNESP University Extension and in 2011 was ranked 3rd in the sixth version of the same Congress.

O Observatório de Política Exterior (OPEx) é um projeto de extensão coordenado pelo Grupo de Estudos Comparados em Política Externa e Defesa (COPEDE/GEDES-SE) da Faculdade de Ciências Humanas e Sociais UNESP-Franca, em parceria com a com a Universidade Federal de Sergipe, com a Universidad Nacional de Rosário (Argentina) e com o Programa de Relações Internacionais da Universidad de La Republica (Uruguai). Seu objetivo é disseminar informação sobre política externa buscando fornecer dados que subsidiem decisões em políticas públicas, pesquisas e formação acadêmica. A equipe da UNESP-Franca elabora informes semanais sobre a política externa do Brasil e da Venezuela, através do cotejamento das notícias referentes à temática veiculadas em jornais diários de ambos os países. Além da produção de informes, a equipe é responsável pela organização dos seguintes eventos mensais: reuniões de leitura nas quais discutimos e analisamos textos acerca da política externa e assuntos relacionados; e CineGEDES, em conjunto com o Observatório de Defesa e Forças Armadas e o Grupo de Elaboração de Cenários Prospectivos (ambos também vinculados ao GEDES), um evento cuja finalidade é promover a discussão sobre política externa, Defesa e Segurança Internacional entre os membros dos grupos a partir de um filme ou documentário. O OPEx é distribuído por meio eletrônico e sua atual lista de subscritores inclui mais de 1.800 endereços, tanto pessoais como institucionais, podendo o conteúdo dos informes também ser acessado através das páginas do grupo nas redes sociais Facebook (/observatoriodepoliticaexterior) e Twitter (@opex_unesp). Em 2009, o OPEB ganhou prêmio de melhor projeto de extensão na área das Humanidades no V Congresso de Extensão Universitária da UNESP e em 2011 ficou em 3º lugar na sexta versão do mesmo congresso.
Keywords: Foreign policy; Brazil; Venezuela; Media; Política externa; Brasil; Venezuela; Mídia